Concept of Market Principles in Early Modern Japan - Sýkora, Jan (Acta Orientalia Vilnensia, 2004)
The period of the Tokugawa regime (1603-1868) corresponds to the age of the European intellectual ferment from which economics emerged as an independent discipline. Though certain parts of Western thought particularly natural science, were studied and propagated by Japanese scholars, the access to the realm of Western political and economic ideas was relatively restricted. At the same time, however, the evolution of the increasing complex Japanese economic system was creating some phenomena - the expansion of commerce, the fluctuation of prices, the intricate division of labour, etc. - which inspired the speculations of European economic thinkers. The article analyzes the particular question of how the leading intellectual figures, including merchant scholars, discussed the intricate problem of market principles.